In silico Analysis of Phospholipase C Proteins Revealed Role During the Growth and Development of Peanut (Arachis hypogaea): Genome-wide analysis of the phospholipase C genes in peanut - Chu, Ha Duc; Tran, Huyen Thi Thanh; Le, Quynh Thi Ngoc; La, Hong Viet; Le, Thuy Thi; Cao, Phi Bang (Journal of Tropical Life Science, 2026)
Phospholipase C (PLC) enzymes, including phosphatidylinositol-specific PLC (PI-PLC) and non-specific PLC (NPC), play central roles in plant lipid signalling, although their genomic features and expression patterns in peanut (Arachis hypogaea) are still insufficiently characterized. This study aimed to identify all PLC family members in the peanut genome and to analyze their structural properties, phylogenetic relationships, and expression profiles across major tissues. Through homology-based searches and domain validation, we identified a total of 10 and 16 ArahyNPC and ArahyPI-PLC genes within the peanut genome, respectively. Phylogenetic analysis classified these PLC proteins into two distinct clades, including NPC and PI-PLC. Gene structure and physicochemical assessment indicated conserved organization and similar protein characteristics within each subfamily. Re-analysis of publicly available RNA-Seq datasets revealed clear tissue-specific expression patterns. Interestingly, ArahyNPC-02 and ArahyNPC-09 showed predominant expression in nodules, while ArahyPI-PLC-15 was expressed mainly in roots. These findings indicate functional diversification among PLC genes in peanut and highlight several candidates that may regulate key developmental processes. The results provide a comprehensive genomic resource that supports future functional studies on PLC-mediated signalling and contributes to breeding strategies aimed at enhancing stress resilience in peanut cultivars. This genome-wide characterization, combined with transcriptomic re-analysis, provides a systematic resource for understanding PLC-mediated lipid signalling in peanut. The identified tissue-preferential PLC candidates offer promising targets for future functional studies aimed at elucidating their roles in development and stress-responsive pathways.